2017
DOI: 10.1016/j.apenergy.2017.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of calcium looping under uncertainty

Abstract: An emerging calcium looping process has been shown to be a promising alternative to solvent scrubbing, which is regarded as the most mature CO2 capture technology. Its retrofits to coal-fired power plants have the potential to reduce both energy and economic penalties associated with the mature CO2 capture technologies. However, these conclusions have been made based on the deterministic outputs of the economic models that have not considered uncertainties in the model inputs. Therefore, this study incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 50 publications
(108 reference statements)
0
38
1
Order By: Relevance
“…These simulation studies were carried out using the aspenONE software. The properties of flue gas, calcium sorbents, thermal oil, and organic fluid were calculated by employing Peng‐Robinson‐Boston‐Mathis (PR‐BM) as property method in the aspenONE simulation software . The biomass composition, operating conditions and system parameters used in this simulation study are shown in Tables and .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These simulation studies were carried out using the aspenONE software. The properties of flue gas, calcium sorbents, thermal oil, and organic fluid were calculated by employing Peng‐Robinson‐Boston‐Mathis (PR‐BM) as property method in the aspenONE simulation software . The biomass composition, operating conditions and system parameters used in this simulation study are shown in Tables and .…”
Section: Methodsmentioning
confidence: 99%
“…A number of successful demonstration projects on CaL all over the world proved its viability as CO 2 capture technology . Its feasibility to retrofit the existing power plants with less energy and economic penalty along with plant load flexibility makes it one of the sustainable CO 2 capture options . Since the CaL reactors operate at sufficiently high temperatures, a large part of the heat can be recovered in the integrated power plant, which reducing the energy penalty.…”
Section: Introductionmentioning
confidence: 99%
“…To account for the uncertainty in the input variables to the techno-economic models, the stochastic approach is implemented by following the procedure presented in Fig. 3 and described in detail elsewhere [22,24]. First, the PtG process model was developed in Aspen Plus ® and the corresponding economic model was built in MS Excel, as detailed in Section Deterministic assessment methodology.…”
Section: Stochastic Assessment Methodologymentioning
confidence: 99%
“…Consideration of the uncertainty in the operating conditions at the process design stage can reduce the occurrence of the failures associated with vibration stresses and unstable operation [25e27], equipment overheating [25], and other failures associated with poor design and increased complexity [28]. By indicating the probabilities of possible outcomes, a stochastic approach to evaluation of the process performance provides a more profound insight into the investment decision-making process and may potentially lead to a different outcomes compared to the deterministic approach [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation